Active screening and interfacility communication of carbapenem-resistant Enterobacteriaceae (CRE) in a tertiary-care hospital. (19th July 2018) - Shimasaki, Teppei; Segreti, John; Tomich, Alexander; Kim, Julie; Hayden, Mary K.; Lin, Michael Y.
Abstract : Background: Hospitals may implement admission screening cultures and may review transfer documentation to identify patients colonized with carbapenem-resistant Enterobacteriaceae (CRE) to implement isolation precautions; however, outcomes and logistical considerations have not been well described. Methods: At an academic hospital in Chicago, we retrospectively studied the implementation and outcomes of CRE admission screening from 2013 to 2016 during 2 periods. During period 1, we implemented active CRE rectal culture screening for all adults patients admitted to intensive care units (ICUs) and for those transferred from outside facilities to general wards. During period 2, screening was restricted only to adults transferred from outside facilities. For a subset of transferred patients who were previously reported to the health department as CRE positive, we reviewed transfer paperwork for appropriate documentation of CRE. Results: Overall, 11, 757 patients qualified for screening; rectal cultures were performed for 8, 569 patients (73%). Rates of CRE screen positivity differed by period, previous facility type (if transferred), and current inpatient location. A higher combined CRE positivity rate was detected in the medical and surgical ICUs among period 2 patients (3.3%) versus all other ward-period comparisons ( P <.001). Among 13 transferred patients previously known to be CRE colonized, appropriate CRE transfer documentation was available for only 4 patients (31%). Conclusions: Active screening for CRE is feasible, and screening patients transferred from outside facilities to the medical or surgical ICU resulted in the highest screen positivity rate. Furthermore, CRE carriage was inconsistently documented in transfer paperwork, suggesting that admission screening or enhanced inter-facility communication are needed to improve the identification of CRE-colonized patients.